Doing Justice to the Environment. (June 2013) - Adshead, Julie
This article examines some of the characteristic features of environmental offences, in particular the ways in which these offences and their treatment in the courts deviate from general principles of criminal law. Despite the fact that environmental offences are often labelled as 'quasi-criminal', there has been long-standing criticism of penalties, particularly the low level of fines in magistrates' courts. The article also considers the possible reasons behind this and argues that, as well as the inexperience of lay magistrates, the perception of environmental crime, fuelled by the strict liability nature of most environmental offences, is a significant factor. The recent introduction of civil sanctions is evaluated along with recommendations for new sentencing powers and sentencing guidelines. The article concludes by considering further suggestions for more effective enforcement of environmental crime in the courts, including the introduction of specialist magistrates' courts and the use of more fault-based offences or a general defence of due diligence for environmental crimes.